Development of glass-ceramics from soda lime silica glass waste by sintering method for opal imitation - D. Bootkul (2018)
© 2017 Elsevier Ltd. All rights reserved. Natural opal, an amorphous, hydrous form of silica (SiO2-n-H2O), has been one of the favored precious gemstones for many centuries. Though beautiful, opal is very fragile and is damaged quite easily. Thus, opals of all varieties have been synthesized experimentally and commercially. The objective of this project was to synthesize and to compare crystalline opals. In this work, the development of powder sintered glass ceramics process based on soda-lime-silica glass waste with silica powder enable jewelry applications. The substantial viscous flow of the glass led to dense products for rapid treatments at relatively low temperatures (900-1,000°C), whereas glass/metal powder interactions resulted in the formation of color agent crystals, provide enhancing optical properties. There is a great potential for such materials with novel functionalities for artificial gemstone application, i.e. opal forming. Several techniques were applied for characterizing the ingots. The chemical analysis was performed by Energy Dispersive X-ray Fluorescence (ED-XRF). The mineralogical compositions of the samples were determined by X-ray diffraction analysis. Raman spectroscopy was applied for optical characterization. The results were compared with a natural common opal. The present experiments demonstrated that the common milky opal can be synthesized by the technique, as the crystalline phase of opal structure was identified by XRD measurement.